The Relationship Between Innovation Skill and Entrepreneurship on Bachelor Students of Sports Education - Alpaslan Baki Ertekin (Journal of Educational Issues, 2024)
It is a fact that the concept of innovation, which is a necessity in every field today, is now indispensable in the sports sector. Especially, it is thought that determining the relationship between the innovation skills of the students in sports education institutions and the entrepreneurship of the students who are candidates to work in the sports sector is important in the development of innovation awareness of the students who will work in this field in the future. The aim of this study is to examine the relationship between innovation and entrepreneurship skills of individuals who receive sports education according to different variables. The study group was formed by the voluntary participation of 240 people, 161 males (67.1%) 79 females (32.9%), studying at the School of Physical Education and Sports at Istanbul Gelişim University, and selected by the purposeful sampling method. In addition to the personal information form, the Individual Innovativeness Scale (IIS) developed by Hurt et al. (1977) and adapted into Turkish by Sarıoğlu (2014), and the Entrepreneurship Scale (ES) developed by Yılmaz and Sünbül (2009) to measure the entrepreneurship levels of university students were used as data collection tools. After the data showed normal distribution, T-Test, ANOVA and Pearson Correlation Test were used in the analyses, and the Tukey test was used to determine the difference between the groups. According to the results, it was determined that the innovation skills and entrepreneurship levels of the individuals’ varied according to different variables. As a result, it was determined that as the innovation skills of students studying at institutions providing sports education increased, their level of entrepreneurship also increased.